Dipeptide-Based Phosphonium Salt Catalysis: Application to Enantioselective Synthesis of Fused Tri- and Tetrasubstituted Aziridines - Wu, Jia-Hong; Pan, Jianke; Wang, Tianli (Synlett, 2019)
Over the past decades, phase-transfer catalysis (PTC), generally based on numerous chiral quaternary ammonium salts, has been recognized as a powerful and versatile tool for organic synthesis in both industry and academia. In sharp contrast, PTC involving chiral phosphonium salts as the catalysts is insufficiently developed. Recently, our group realized the first enantioselective aza-Darzens reaction for preparing tri- and tetrasubstituted aziridine derivatives under bifunctional phosphonium salt catalysis. This article briefly discusses the recent development in asymmetric reactions (mainly including nucleophilic additions and cyclizations) promoted by chiral quaternary phosphonium salt catalysts. We expect that more catalytic asymmetric reactions will be developed on the basis of such new phase-transfer catalytic systems in the near future.
Keywords: bifunctional phosphonium salts; multisubstituted aziridines; asymmetric cyclization; aza-Darzens reaction; phase-transfer catalysis